Laryngeal mask airway use during neonatal resuscitation: a survey of practice across newborn intensive care units and neonatal retrieval services in Australian New Zealand Neonatal Network. (19th September 2020) - Goel, Dimple; Shah, Dharmesh; Hinder, Murray; Tracy, Mark
Abstract : This is an Australia New Zealand Neonatal Network (ANZNN) wide survey to identify current practice and guide future practice improvement for the use of laryngeal mask airway (LMA) during neonatal resuscitation. An online questionnaire containing 13 questions was sent out to all tertiary neonatal centres ( n = 29 units) and neonatal transport units ( n = 4) within ANZNN. The non‐tertiary (level‐II) centres were not included. Response from a senior neonatologist at each centre was received and evaluated. Twenty‐two services (67%) had LMA available; of that only, 40% felt the competency of staff to be adequate; and 59% had routine training in LMA use. During neonatal resuscitation, 68% units reported using LMA if endotracheal intubation was unsuccessful after two or more failed intubation attempts and only 18% used it before intubation if face mask ventilation was inadequate. This survey highlighted variations in practice across the tertiary neonatal centres in ANZNN network. One‐third of the units lack LMA availability and the units with LMA, face concerns of underutilisation and lack of skills for its use.